Cultural-policy shifts from the desertion and destruction to the conservation of common heritage: 19th-century Ottoman churches in Turkish Thrace - Bilgic Elmas, Melis; Binan, Can Sakir (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeThe paper critically evaluates processes regarding the transformation of cultural properties remaining of those Turkey inherited from non-Muslim Ottoman communities through the case of 19th-century churches in Turkish Thrace within the framework of common heritage.Design/methodology/approachIn the first phase, existing literature is reviewed to trace the evolution of the common heritage concept and to examine changing viewpoints towards non-Muslim cultures after the establishment of the Turkish Republic (1923). Building on this conceptual groundwork, data collection involved fieldwork and archival research across Turkish Thrace between 2023 and 2025. Through fieldwork, the extant 19th-century churches in the region were identified, and five were selected for detailed case study. The construction and transformation processes of these five churches were investigated using primary archival sources and interpreted through the lens of the common heritage perspective.FindingsContextualizing the transformation and (lack of) conservation of the 19th-century churches within the changing viewpoints towards different cultures in the country reveals the historical milestones that dictated this transformation. The attitudes towards the extant churches in Turkish Thrace are categorized as reuse with original function, reuse with different function, desertion, and destruction. The acceptance of 19th-century churches as common heritage will contribute to the longevity of the buildings in all of these categories. For this purpose, potential approaches have been outlined in order to raise awareness for their conservation.Originality/valueThis study introduces a comprehensive and methodical approach to evaluate the transformation of 19th-century churches in Turkish Thrace that lost their original function and congregation after mass migrations, examining the interventions and actors involved through previously unpublished archival documents. The approach is formulated within the framework of common heritage. It holds broader international relevance beyond the regional context, offering a model adaptable to other multicultural and post-conflict heritage contexts worldwide. The study further proposes new approaches for the conservation of these churches by taking into account legal, national, and cultural dynamics.
Keywords: Common heritage; Turkish Thrace; Multiculturalism; 19th-century churches; Transformation; Reuse; Desertion; Destruction; Science & Technology - Other Topics